Strength Analysis and Repair Strategy of Aged Steel Jetty Pile - Riyanto, Raditya Danu; Syahroni, Nur; Mulyadi, Yeyes (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2021)
Indonesia has 95.161 km coastal lines with a total of 17.504 islands. With this nature, Indonesia has 1.226 ports, with a total accumulated length of up to 92 km. However, not all these ports are in proper condition. For ports that have steel jetty piles, corrosion is one of the problems. This paper provides technical experience and methodology for analyzing the pier's corrosion conditions and evaluating existing corrosion's effect on its strength. The survey methodology and required data, including a survey of cathodic protection, visual conditions, and pile thickness, are discussed in this paper. The static strength analysis of the existing state structure was carried out. This article provides repair strategies, including repair methods and a study of the number of piles repaired. This methodology results in the recommendations for pile repair strategies and guidance on effective analytical methods in determining the number of repaired piles for aged steel jetty pile repair.